Pemeliharaan CT(Current Transformer) sebagai Konversi Arus pada Gardu Induk Rangkas Kota 70 KV - Minhaz Tolibin; Mohammad Fatkhurrokhman (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
The Substation is a sub-system or a unit of the electric power distribution (transmission) system. Distribution (transmission) is a sub-system of the electric power system. This means that the substation is a sub-sub-system of the electric power system. Therefore, one of the most important equipment in the substation is the current transformer (CT) which is a very important equipment in the substation, where this device is used to convert a large current value into a smaller current value for measurement and protection purposes. The Current Transformer must be in good condition in order to be able to transform the current accurately and thoroughly. The research method carried out in the form of literature studies is to find and collect various references from books and journals as well as previous research related to the research title that the author took, in addition to that the author takes and collects related data needed in the form of CT maintenance data at PT. PLN (Persero) ULTG Rangkasbitung then analyzed all the data that had been collected. The measurement of isolation resistance is carried out at the beginning of the test intended to find out the isolation conditions of the current transformer at an early stage and to avoid subsequent test failures. The test results of the isolation resistance of primary-ground CT in phase R are 130000 MΩ, which means that the CT is still in good condition. Meanwhile, the delta tan test on CT with R phase is 0.17%, which means that the ct is also still in good condition.